До питання про “особливі печі” у давньому Звенигороді на Білці - Гупало, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article is dedicated to analyses of results of excavations on the territory of western part of hill-fort in Zvenyhorod (Pustomyty district, L’viv region) – western area of outer part of annalistic city. Investigations were carried out in 1954–1969 (with interruptions), when complex, which consists of 44 ovens was discovered. But this material is still not published. Series of facts, connected with stratigraphy of objects, their constructional peculiarities and character of finds were elucidated on the base of research of scientific reports. Detail analyses of this data allow the author to present some questions about verification of dating, chronology and functions of discovered objects. These issues are very important for explorations of general character of constructional structure of the city.